Pengaruh Subject Specific Pedagogy IPA Berbasis Lab Work Terhadap Sikap Rasa Ingin Tahu dan Teliti Siswa - Elyas Djufri; Trio Ardhian; Shanta Rezkita (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2018)
This research aimed to find out the effect of science Subject Spesific Pedagogy based lab work on: (1) the curiosity of the students, (2) the precise of the students, (3) the curiosity and precise of the students. This research is a quantitative using a quasi experimental design with nonequivalent control group design. Population of this research was all students of class IX SMP Integral Hidayatullah Tolitoli. The sample of this research was selected through cluster random sampling, namely class IX A as an experiment class and class IX B as a control class. This research used a enclosed questionaire instrument that was adapted from Hermanto research. The data analysis used the ANOVA and MANOVA. The results show that: (1) the implementation of science subject specific pedagogy based lab work gives a significantly more positive effect to the curiosity of the students than convensional learning, (2) the implementation of science subject specific pedagogy based lab work gives a significantly more positive effect to the precise of the students than conventional learning, and (3) the implementation of science subject specific pedagogy based lab work gives a significantly more positive effect to the curiosity and precise of the students than convensional learning does.